Crowded Trichophycus ichnofabrics in the early Ordovician successions of central Iran: insight into the Ordovician radiation. (5th November 2020) - Bayet‐Goll, Aram; Uchman, Alfred; Daraei, Mehdi; de Carvalho, Carlos Neto
Abstract : The Tremadocian‐to‐Floian siliciclastic deposits of the Shirgesht Formation in the Kalmard Block of central Iran show abundant occurrences of the mid‐tier Trichophycus venosus, a common ichnotaxon in the archetypical Cruziana ichnofacies. This trace fossil records a considerable increase in exploitation of offshore infaunal ecospace in comparison with older formations. Here, Trichophycus is relatively long and wide, with numerous and deep successively stacked causative burrows, which form dense burrow systems building the Crowded Trichophycus ichnofabric (CTI). Such development of CTI and the increase in depth of bioturbation had a negative effect on preservation of shallow‐tier traces, for example arthropod burrows and trackways. This resulted in decreasing abundance of trilobite‐produced trace fossils towards the top of the succession. The palaeobiological and palaeoecological interpretation of CTI points to stable habitats in muddy substrates above the storm wave base with high content of food and oxygen in pore waters, low‐energy hydrodynamic regimes and a long colonization window. Moreover, the architecture and the morphological features of Trichophycus suggest a combined dwelling‐feeding activity of the resident fair‐weather producer showing the K‐selected/climax strategy. The ethology of the producer, palaeoecological interpretations and taphonomic signatures revealed that it preferred dewatered, compacted muddy substrates (firmgrounds) in offshore settings, which might be related to minor hiatuses or short‐lived discontinuities. Although the appearance of Trichophycus is concomitant to the earliest Cambrian agronomic revolution, it was uncommon until the early Ordovician, when locally it records infaunalization related to the Great Ordovician Biodiversification Event.